LANSIA BEKERJA SEBAGAI TUKANG BECAK DI KOTA TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Andra Nadia Audina; Resdati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the rational considerations of elderly individuals inchoosing and maintaining their work as pedicab drivers in Tembilahan City, IndragiriHilir Regency, and to identify the obstacles they face. The study was motivated bythe increasing number of elderly who continue to work in the informal sector due toeconomic limitations and lack of social security. The research used a qualitativedescriptive approach with in-depth interviews, observation, and documentation. Thesubjects in the study were 6 informants, 5 informants who worked as pedicabdrivers, and 1 informants were customers. James S. Coleman’s rational choicetheory served as the framework. The results show that the main motivations aremaintaining economic independence, filling spare time, and self-actualization.Challenges include physical limitations, reduced customers, and competition withmodern transportation. The findings indicate that continuing to work as pedicabdrivers is an adaptive strategy for elderly survival.